2020
DOI: 10.1089/vbz.2019.2591
|View full text |Cite
|
Sign up to set email alerts
|

Feline-Human Zoonosis Transmission in North Africa: A Systematic Review

Abstract: Throughout human history, domestic animal species have represented a unique zoonotic disease risk for the transmission of pathogens ranging from viral, bacterial, parasitic, and fungal. In North Africa, cats have a particularly long record and occupy a specialized niche within many communities. This systematic review was conducted to analyze the current and historical literature documenting the breadth and variety of zoonoses in North Africa, specifically relating to the domesticated feline. Multiple electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
(68 reference statements)
0
4
0
2
Order By: Relevance
“…Reports show that F. hepatica is endemic in Europe, the Americas, Oceania, Africa and Asia while F. gigantica has a focal distribution in Africa and Asia (Ashrafi et al 2006 ; Kasahara et al 2021 ; Le et al 2008 ; Moghaddam et al 2004 ; Seid & Melese 2018 ; Valero et al 2009 ). Various animals, such as sheep, goats, cattle, buffalos, horses, donkeys, camels and rabbits, have shown very high infection rates in different areas (Farag 1998 ; Karshima, Bata & Bobbo 2016 ; Peterson & Barnes 2020 ). Initially, human infection with fascioliasis was very sporadic; however, in recent times, clinical cases and outbreaks were reported (Haseeb et al 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reports show that F. hepatica is endemic in Europe, the Americas, Oceania, Africa and Asia while F. gigantica has a focal distribution in Africa and Asia (Ashrafi et al 2006 ; Kasahara et al 2021 ; Le et al 2008 ; Moghaddam et al 2004 ; Seid & Melese 2018 ; Valero et al 2009 ). Various animals, such as sheep, goats, cattle, buffalos, horses, donkeys, camels and rabbits, have shown very high infection rates in different areas (Farag 1998 ; Karshima, Bata & Bobbo 2016 ; Peterson & Barnes 2020 ). Initially, human infection with fascioliasis was very sporadic; however, in recent times, clinical cases and outbreaks were reported (Haseeb et al 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cases of feline leishmaniasis have been described in South American countries [3][4][5][6][7][8], Europe [9][10][11], Asia [12], and Africa [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, although reports of leishmaniasis in cats are increasing, the role of this animal in the eco-epidemiology of the disease remains uncertain. The lack of early diagnosis of FeL in endemic areas suggests that cats continue to present potential risks of transmission of leishmaniasis to vectors since studies have shown that infection in cats can remain active for long periods; thus, the risk of infectivity to sandflies is maintained [3].…”
Section: Introductionmentioning
confidence: 99%
“…La tenencia de animales de compañía ha aumentado y con ello la potencial infección con agentes zoonóticos por contacto cercano con mascotas (Acosta et al, 2017;Vitale et al, 2019;Jenkins, 2020). Estos agentes se propagan en la interfaz hombre-animal-medio ambiente, donde personas y animales interactúan entre sí (FAO/OMS/OIE, 2019; Wulcan et al 2019;Peterson & Barnes, 2020).…”
Section: Introductionunclassified
“…Los parásitos ciclozoonóticos asociados a perros y gatos ocasionan múltiples enfermedades al hombre (Vilca de Díaz & Melo-Anccasi, 2013;Nunes et al, 2018;Ferraz et al, 2020;Jenkins, 2020;Ketzis et al, 2020), representando un riesgo potencial para la salud humana (Ruiz et al, 2015;Peterson & Barnes, 2020). La alta frecuencia de parásitos intestinales zoonóticos en perros y gatos hace necesarias medidas correctivas y preventivas desde la salud pública para su control (Ortiz-Álvarez, 2015;Sarmiento-Rubiano et al, 2018;Rivero et al, 2020) & Melo-Anccasi, 2013;Ruiz et al, 2015;Rosado-Aguilar et al, 2016;García-Galán et al, 2017;Geng et al, 2018;Sarmiento-Rubiano et al, 2018;López-Osorio et al, 2020;Rostami et al, 2020), lo que evidencia una parasitofauna común.…”
Section: Introductionunclassified